Simulation study on the effect of CH4 blending on the propagation characteristics of spontaneous combustion flame of high-pressure hydrogen leakage - Gan Cui; Huan Liu; Yilong Chen; Wei Wang; Qingsen Ren; Xiao Xing; Jianguo Liu (Case Studies in Thermal Engineering)
Hydrogen, as a clean energy carrier, plays a vital role in advancing the energy transition. However, its high flammability and explosion risks pose significant challenges to application safety. This study employs numerical simulations to investigate the effects of CH4 blending at varying concentrations on auto-ignition flame propagation characteristics during high-pressure hydrogen release. The analysis focuses on the mechanisms through which CH4 blending influences shock wave intensity, ignition delay, and flame propagation behavior. The results demonstrate that CH4 blending significantly reduces shock wave intensity, prolongs the ignition delay time, and suppresses the integrity and intensity of flame propagation both inside and outside the pipe. These effects intensify with increasing CH4 concentration. The findings provide theoretical support for the safety design of high-pressure hydrogen systems operating under CH4-blended conditions, contributing substantially to enhancing the safe utilization of hydrogen energy in industrial and transportation settings.